1998
DOI: 10.1088/0953-2048/11/10/020
|View full text |Cite
|
Sign up to set email alerts
|

Technology of Bi, Pb-2223 tape fabrication with Ag and Ag alloy sheaths for electric power systems

Abstract: Bi-2223 multifilamentary tapes with Ag and Ag alloy (AgMn, AgPdAu) sheaths have been fabricated using the OPIT technique. From thermal analysis and XRD investigations one can conclude that the formation rate and microstructure of the Bi-2223 phase is strongly influenced by the occurrence of a liquid phase during the precursor transformation. The parameters of the thermomechanical treatment were optimized such that values of (77 K, 0 T) could be achieved for tapes of a length up to 550 m, independent of the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…This behaviour is explained by taking into account the type of strain experienced by the core in the two cases: for tensile loading the whole cross sectional area experiences the same strain, while it is distributed equally from the neutral axis for bend strains. (4) The mechanical properties of the Ag-Cu alloy sheathed tapes are as good as those reported for other types of alloy sheathed tapes [24][25][26]. The critical stress values (σ c ) of the AgCu9 and AgCu6 samples are 104 and 84 MPa, respectively, while that of the AgMgNi tape [26] is 102 MPa.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…This behaviour is explained by taking into account the type of strain experienced by the core in the two cases: for tensile loading the whole cross sectional area experiences the same strain, while it is distributed equally from the neutral axis for bend strains. (4) The mechanical properties of the Ag-Cu alloy sheathed tapes are as good as those reported for other types of alloy sheathed tapes [24][25][26]. The critical stress values (σ c ) of the AgCu9 and AgCu6 samples are 104 and 84 MPa, respectively, while that of the AgMgNi tape [26] is 102 MPa.…”
Section: Discussionmentioning
confidence: 56%
“…A remarkable improvement in the mechanical properties of Bi-2223/AgMg tapes was reported by Goldacker et al [24]. Fischer et al [25] reported the use of AgMn and AgPdAu as sheath materials with improved tensile strength. Also, it is reported that the use 1 Corresponding author.…”
Section: Introductionmentioning
confidence: 80%
“…The microhardness of the specimen increases uniformly with increasing deformation up to 80%. Fischer et al [4,5] reported an increase of microhardness of AgMn x (x = 0.06-0.4) when heat treated at 817-820 • C in an oxidized atmosphere. An H V = 115-150 increase was attributed to the formation of submicron Mn oxide or Mn-O clusters with a stable size and structure as a result of lengthy annealing times.…”
Section: Resultsmentioning
confidence: 99%
“…However, the mechanical strength of Bi-2223 tapes is remarkably low because the sheath material of Bi-2223 superconducting tapes must be used only Ag and/or Ag based alloy in order to obtain the high J c performance [7][8][9][10]. HTS tapes are not mechanically robust, having low tolerance to tensile and bending stresses encountered during processing and the fabrication and operation of devices.…”
Section: Introductionmentioning
confidence: 99%